2017
DOI: 10.1038/ncomms14405
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal degradation of the neuronal stress-protective transcription factor HSF1 in Huntington’s disease

Abstract: Huntington's Disease (HD) is a neurodegenerative disease caused by poly-glutamine expansion in the Htt protein, resulting in Htt misfolding and cell death. Expression of the cellular protein folding and pro-survival machinery by heat shock transcription factor 1 (HSF1) ameliorates biochemical and neurobiological defects caused by protein misfolding. We report that HSF1 is degraded in cells and mice expressing mutant Htt, in medium spiny neurons derived from human HD iPSCs and in brain samples from patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
253
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(284 citation statements)
references
References 67 publications
16
253
1
Order By: Relevance
“…al. (17) and another recent study have shown the involvement of Fbxw7 in the degradation of Hsf1 when it is phosphorylated on S303/S307 impacting cancer progression, and aggregation of poly Qcontaining huntingtin protein (18). In one study, it was shown that in melanoma cells expressing lower Fbxw7α levels, Hsf1 is stabilized leading to higher levels of Hsps and more aggressive melanomas and metastasis (17).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…al. (17) and another recent study have shown the involvement of Fbxw7 in the degradation of Hsf1 when it is phosphorylated on S303/S307 impacting cancer progression, and aggregation of poly Qcontaining huntingtin protein (18). In one study, it was shown that in melanoma cells expressing lower Fbxw7α levels, Hsf1 is stabilized leading to higher levels of Hsps and more aggressive melanomas and metastasis (17).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, substitution of serine residues 303 and 307 to glutamic acid or alanine led to repression or derepression, respectively of the Hsf1 activation domain, suggesting that these phosphorylation sites exert intermolecular influence on Hsf1 protein (11). More recent evidence suggest that in addition to transcriptional repression of Hsf1 under normal physiological growth conditions, the phosphorylation of S303/S307 facilitates its binding to Fbxw7α ubiquitin ligase leading to its degradation through the SCF (Skp1-Cul1-Fbox) complex (17,18,35). Both Kourtis, et.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations